2002
DOI: 10.1103/physreve.66.036410
|View full text |Cite
|
Sign up to set email alerts
|

Radiative ablation to low-Zmatter

Abstract: Eight beams of 0.35-microm laser with pulse duration of about 1.0 ns and energy of 260 J per beam were injected into a cylindrical cavity to generate intense x-ray radiation on the Shengguang II high power laser facility. Plastic foils with a thickness in the range of about 3.0-45 microm were attached on the diagnostic hole of the cavity and ablated by the intense x-ray radiation. The radiative energy transport through plastic foils with different thicknesses has been studied experimentally. The burn-through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In particular, the application of a perpendicular magnetic field aids the Wigner crystallization, 5,6 the formation of strongly correlated many-body states 7,8 and induces ground state multiplicity transitions. 9 From the theoretical side, the 'exact' numerical diagonalization method 5,10,11,12,13,14,15,16 is of profound importance as a reference for approximate treatments. With the presently available computing power this approach has been successfully applied to compute the electronic structure of few-electron quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the application of a perpendicular magnetic field aids the Wigner crystallization, 5,6 the formation of strongly correlated many-body states 7,8 and induces ground state multiplicity transitions. 9 From the theoretical side, the 'exact' numerical diagonalization method 5,10,11,12,13,14,15,16 is of profound importance as a reference for approximate treatments. With the presently available computing power this approach has been successfully applied to compute the electronic structure of few-electron quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the favorable deposition of constituent atoms in certain crystal orientations promotes faster directional growth relative to the other facets, thereby enlarging the proportion of slow-growing facets. 39,40 Therefore, adsorption calculations for Pd atoms were carried out to compare the crystal growth capability of each low-index facet under different reduction conditions. A Pd atom was adsorbed onto the Pd surface where either CO or H molecules had already achieved full coverage.…”
Section: Elucidation Of the Formation Of Tetrahedron-shaped Pd Nanopa...mentioning
confidence: 99%
“…For B1 and B2, electrons in the S orbitals undergo a number of transitions where p and d levels are successively populated in order to minimize the Coulomb repulsion. Eventually, the so called maximum density droplet (MDD), 72,73,74,75 i.e., the densest spin-polarized configuration possible, is reached. For B3 this phase is not observed at B = 0 in the range of B ⊥ explored (Fig.…”
Section: B Few-particle Statesmentioning
confidence: 99%